2021
DOI: 10.3390/s21165435
|View full text |Cite
|
Sign up to set email alerts
|

An Indoor Navigation Methodology for Mobile Devices by Integrating Augmented Reality and Semantic Web

Abstract: Indoor navigation systems incorporating augmented reality allow users to locate places within buildings and acquire more knowledge about their environment. However, although diverse works have been introduced with varied technologies, infrastructure, and functionalities, a standardization of the procedures for elaborating these systems has not been reached. Moreover, while systems usually handle contextual information of places in proprietary formats, a platform-independent model is desirable, which would enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The two studies with a score of 10 are released in 2007 and 2020. The one 59 with a score of 3 is published in 2021. Therefore, the design of the studies in SW technology relies on the experience and preferences of different researchers regardless of when the studies are finished.…”
Section: Discussionmentioning
confidence: 99%
“…The two studies with a score of 10 are released in 2007 and 2020. The one 59 with a score of 3 is published in 2021. Therefore, the design of the studies in SW technology relies on the experience and preferences of different researchers regardless of when the studies are finished.…”
Section: Discussionmentioning
confidence: 99%
“…According to the review of literatures and research related to the use of AR, it was found that AR is currently used in several aspects, i.e., navigation application development [18], [19] [20], [21], [22] for tourism [23], [24], education or learning [25], marketing [26], [10], product presentation, and product search [11], [12], [13], [14], [15], [16], [17]. The details of the review of related literatures and research are as follows.…”
Section: Related Workmentioning
confidence: 99%
“…Web-based AR can help users navigate strange places [2,10,11]. Web AR overlays can offer visual directions, highlight points of interest, or display more information about the surroundings by utilising a mobile device's camera and GPS capabilities [1,12].…”
Section: Introductionmentioning
confidence: 99%